The diversification of inequality. (22nd December 2017) - Brynin, Malcolm; Longhi, Simonetta; Zwysen, Wouter
Abstract: We examine intersectionality on the basis of increasingly complex interactions between gender and ethnic groups, which we argue derive from the growing diversity of these groups. While we critique the concept of superdiversity, we suggest that increased diversity leads to a 'diversification of inequality'. This is characterised by an increasing incidence of inequality through the growth in migration and of the size and variety of ethnic minorities, and by a weakening of specific inequalities. We demonstrate this using the Labour Force Survey and conclude that there is a clear diversification of inequality but also that ethnicity is a more potent source of inequality than gender. Diversity also increases the reach of inequality through producing and increasing the number of intersections.